Ethical consultation in the healthcare field - Cattorini, Paolo Marino (Medicina e Morale, 2023)
The role, identity and responsibility of the so called expert in bioethics is a main, urgent issue in the contemporary medical and ethical debate upon the mission of the health care institutions and upon the need for Ethical Services/Departments in Hospital and Research Centers. An advice by the Comitato nazionale per la Bioetica is commented. Questions are raised about the philosophical or rather clinical nature of the bed-side ethics consultation and about the competences and professional skills of the consultant (non-directive posture, the aim of reaching a share decision, the improvement of the patients' autonomy and interest). The features of Ethics Research Centers are also analyzed